Identification of Different Extracellular Vesicles in the Hydatid Fluid of Echinococcus granulosus and Immunomodulatory Effects of 110 K EVs on Sheep PBMCs - Yang, Jing; Wu, Jin'en; Fu, Yong; Yan, Lujun; Li, Yating; Guo, Xiaola; Zhang, Yong'e; Wang, Xiaoqiang; Shen, Yujuan; Cho, William C.; Zheng, Yadong (Frontiers in Immunology, 2021)
Echinococcosis is one of the 17 neglected tropical diseases, being mainly caused by Echinococcus granulosus. Extracellular vesicles (EVs) play an essential role in the host-parasite interplay. However, the EVs in the hydatid fluid (HF) of E. granulosus are not fully characterized. Herein, three different types of HF EVs, designated as 2 K, 10 K and 110 K EVs based on centrifugal force used, were morphologically identified. A total of 133, 110 and 937 proteins were identified in 2 K, 10 K and 110 K EVs, respectively, 11 of which were commonly shared. Moreover, 11, 8 and 25 miRNAs were detected, respectively, and all of 7 selected miRNAs were validated by qPCR to be significantly lower abundant than that in protoscoleces. It was further showed that 110 K EVs were internalized by sheep peripheral blood mononuclear cells (PBMCs) in a time-dependent manner, and induced IL-10, TNF-α and IRF5 to be significantly upregulated and IL-1β, IL-17 and CD14 to be significantly downregulated (p < 0.05). These data demonstrate the physical discrepancy of three HF EVs and an immunomodulatory effect of 110 K EVs on sheep PMBCs, suggesting a role in immune responses during E. granulosus infection.